Media Ludo Kebhinekaan pada Pembelajaran IPS Keberagaman Budaya (Studi Analisis Kebutuhan pada Siswa Kelas IV Sekolah Dasar) - Nabila, Ghalda; Hanim, Wirda; Hasanah, Uswatun (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
Research conducted at SDN Paseban 18 Pagi saw the boredom of students in learning, especially in social studies subjects, due to the lack of use of supportive learning media. In addition, researchers also noted an attitude of intolerance among students regarding differences. This encouraged researchers to analyze the need for developing ludo kebhinekaan learning media to improve social studies learning that pays attention to cultural diversity in grade IV. This study involved 1 teacher and 14 grade IV learners at SDN Paseban 18 Pagi. The development method used is the ADDIE Model, which involves five stages: Analysis, Planning, Development, Implementation, and Evaluation. At the needs analysis stage, researchers used observation and questionnaires to collect data from teachers and grade IV students. The results showed that 78% of students expressed a lack of interest in social studies due to monotonous learning without the use of learning media, while 69% of teachers saw weaknesses in improving students' tolerance attitudes. This research became the basis for the development of learning media that is expected to overcome the lack of interest of students in social studies while improving their understanding and tolerance attitude towards diversity.